Islamic Cultural History Learning Problems in Class Vii ‎MTSN 1 Bengkalis: Analysis of Students' Difficulties in ‎Understanding The Material and Their Solutions - Ariga Sahmadi; Muhammad Yassir ‎ (el-Tarbawi : Jurnal Pendidikan Agama Islam, 2026)
The urgency of this research lies in the importance of learning Islamic Cultural History (ISH), which not only conveys historical information but is also rich in Islamic values ​​that can shape students' character, morality, and religious insight. This study aims to analyze the problems faced by seventh- grade students of MTsN 1 Bengkalis in learning Islamic Cultural History (ISH), particularly in the aspect of understanding the material. This study uses a qualitative approach with a phenomenological design to explore the subjective experiences of teachers and students during the learning process. The study population included 32 ISH students and 3 ISH teachers, with a purposive sampling technique to select participants based on their direct experiences in ISH learning. Data collection instruments consisted of semi-structured interviews, participant observation, and documentation. Data were analyzed thematically by identifying key themes such as difficulties in understanding historical figures, obstacles in memorizing chronology, and limitations of visual media. The results showed that students' difficulties were caused by low reading interest, monotonous teaching methods, limited learning media, and time constraints. In addition, students' emotional and cognitive factors also influenced their understanding of historical material. Data validation was conducted through triangulation of sources and techniques, as well as member checking to ensure the validity of the results. As a solution, the implementation of varied learning methods such as storytelling, group discussions, and the use of technology-based interactive media is recommended to increase student engagement and understanding. These findings are expected to be contribution to improving SKI learning strategies to be more effective, contextual, and enjoyable in madrasas.